(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
القيادة البارعة تأثيرها في ريادة الاعمال المؤسسية " بحث تحليلي في شركة التأمين العراقية العامة " The Impact of Ambidextrous Leadership on Institutional Entrepreneurship "An Analytical Research in the Iraqi General Insurance Company علي مظهر عبد المهدي وزارة المالية، شركة التأمين العراقية amudher35@gmail.com المستخلص : يهدف البحث الحالي التعرف على مستوى القيادة البارعة في وزارة المالية (شركة التأمين العراقية العامة) ، وبيان أثرها في تفعيل المؤسسة الريادية ، إذ تعامل البحث مع مستوى القيادة البارعة كمتغير مستقل من خلال أبعادها (السلوك المنفتح، السلوك المنغلق، المرونة الزمنية) ، وريادة الاعمال المؤسسية كمتغير تابع من خلال أبعادها (الابتكار، التفرد، المباداة، وتحمل المخاطر). إذ تحتاج هذه الشركة الى أسلوب قيادي بارع يمكن اعتماده في تحويل الشركة الى شركة ريادية، فضلاً عن التغلب على المشكلات والصعوبات التي تواجهها، في ظل المشكلات والتحديات التي تواجه شركة عينة البحث وعليه تحددت مشكلة البحث بعدد من التساؤلات كان أهمها، هل توجد علاقة بين القيادة البارعة وريادة الاعمال المؤسسية في وزارة المالية(شركة التأمين العراقية) ، ومن اجل تحقيق أهداف البحث والإجابة عن تساؤلاتها تم اختيار وزارة المالية (شركة التأمين العراقية العامة) ميدانيا للجانب التطبيقي للبحث، وقد اعتمد الباحث على الاستبانة كأداة لجمع البيانات، وزعت (95) استبانة على عينه من العاملين في الشركة في مجال تقديم الخدمات التأمينية، وقد تضمن البحث فرضيات للاختبار علاقة الارتباط والتأثير بين متغيري البحث، وتم اعتماد على البرنامج الإحصائي (SPSS.V.26) و(Microsoft Excel v.2013) لتحليل النتائج، حيث توصل البحث إلى عدد من الاستنتاجات واهمها: هناك تأثيراً إيجابياً للقيادة البارعة (سلوك المنفتح والمنغلق والمرونة الزمنية) في ريادة الاعمال المؤسسية، بمعنى أن قيام شركة التأمين العراقية العامة بتفعيل ممارسات القيادة البارعة له تأثير ايجابي في بناء مؤسسة ريادية. فضلاً عن عدد من التوصيات منها، ضرورة قيام ادارات العليا في شركة عينة البحث بتحفيز المرؤوسين لتقديم أفضل ما لديهم من اقتراحاتهم وآرائهم بشأن المشكلات التي تعترضهم ، وبالإضافة الى افكارهم بخصوص مستقبل الشركة عينة البحث من منطلق انهم اكثر قرباً من الواقع العملي مما يجعلهم اكثر استعداداً لتوليد الافكار المبدعة في الوقت المناسب. الكلمات المفتاحية: القيادة البارعة، ريادة الاعمال المؤسسية، وزارة المالية – شركة التأمين العراقية. Abstract: The Current Research Aims to Identify The Level Of Ambidextrous Leadership In The Ministry Of Finance (The Iraqi General Insurance Company), And To Demonstrate Its Impact On Activating The Entrepreneurial Institution. The Research Dealt with the Level of Leadership Ambidextrous as an Independent Variable through Its Dimensions (Open Behavior, Closed Behavior, Time Flexibility), and Institutional Entrepreneurship. As A Dependent Variable through Its Dimensions (Innovation, Uniqueness, Initiative, and Risk Tolerance). This Company Needs a Brilliant Leadership Style That Can Be Adopted In Transforming The Company Into An Entrepreneurial Company, In Addition To Overcoming The Problems And Difficulties It Faces, In Light Of The Problems And Challenges Facing The Research Sample Company. Accordingly, The Research Problem Was Determined by A Number Of Questions, The Most Important Of Which Was: Is There A Relationship Between Leadership And... Ingenuity and Institutional Entrepreneurship in the Ministry of Finance (The Iraqi Insurance Company). In Order to Achieve The Objectives Of The Research And Answer Its Questions, The Ministry Of Finance (The Iraqi General Insurance Company) Was Chosen In The Field For The Applied Aspect Of The Research. The Researcher Relied On The Questionnaire As A Tool For Collecting Data. (95) Questionnaires were distributed on a Sample of the Company’s Employees in the Field of Providing Insurance Services, The Research Included Hypotheses to Test the Correlation and Influence Relationship between the Two Research Variables. The Statistical Program (SPSS.V.26) And (Microsoft Excel V.2013) Were Relied Upon To Analyze The Results. The Research Concluded to a Number of Conclusions, The Most Important of Which Are: There Is a Positive Effect of Ambidextrous Leadership (Open and Closed Behavior and Time Flexibility) On Institutional Entrepreneurship, Meaning That The Iraqi General Insurance Company’s Activation of Ambidextrous Leadership Practices Has a Positive Impact in Building an Entrepreneurial Institution. In Addition To A Number Of Recommendations, Including The Need For Senior Management In The Research Sample Company To Motivate Subordinates To Present Their Best Suggestions And Opinions Regarding The Problems They Encounter, In Addition To Their Ideas Regarding The Future Of The Research Sample Company, On The Basis That They Are Closer To Practical Reality, Which Makes Them More Prepared To Generate Creative Ideas At The Right Time